(untitled) (Acta Scientiarum. Biological Sciences, 2021)
The selective activity of an antineoplastic drug is related to its ability to promote cytotoxic action on tumor cells and preserve the integrity of non-neoplastic cells. Beta-lapachone is extracted from the sawdust of Ipe wood, a thick bark tree from the Ipe wood found in the Brazilian Cerrado biome. This study aimed to evaluate the cytotoxic action of beta-lapachone in an endothelial cell line. The EA.hy926 cells were seeded in two groups, G1 and G2, cultured and exposed to beta-lapachone at concentrations of 0.0, 0.01, 0.03, 0.1, 0.3, 1 and 3 Î¼M for 24 hours. G1 remained under normal cultivation conditions and G2 was subjected to oxidative stress through an ischemia and reperfusion assay, in a deoxygenated sealed chamber. The cytotoxicity assay was performed using the tetrazolium reduction method. In G1, the cytotoxicity ranged from 0.0 to 10.0%; and in G2 between 0.0 and 6.3%. No statistically significant difference was observed between the obtained values. Moreover, we found no cytotoxic action of beta-lapachone on endothelial cells, and the results point out that the drug might have preserved the cell’s integrity against oxidative stress under the conditions of this experiment. This promising result suggests the possibility of beta-lapachone as a chemotherapy drug with selective activity.